Combined treatment of primary vitreoretinal lymphomas significantly prolongs the time to first relapse. Issue 11 (29th January 2018) - Klimova, Aneta; Heissigerova, Jarmila; Rihova, Eva; Brichova, Michaela; Pytlik, Robert; Spicka, Ivan; Mrazova, Katerina; Karolova, Jana; Svozilkova, Petra
Abstract : Background: Vitreoretinal lymphomas belong to the family of central nervous system (CNS) lymphomas. The optimal approach for the treatment of isolated primary vitreoretinal lymphoma is unclear because of the lack of large comparative clinical series. Combination of intravitreal and systemic chemotherapy is recommended in many reports. The aim of our retrospective study was to compare the survival rate and prognosis of patients with vitreoretinal lymphoma with and without CNS involvement. Methods: Twenty patients with vitreoretinal lymphomas were observed between the years 2004and2016, 10 patients with primary vitreoretinal lymphoma and 10 with primary CNS lymphoma. To compare survival rates, we included 53 patients diagnosed with primary CNS lymphoma without vitreoretinal involvement between the years 2002and2011 from our haemato-oncology department. Results: The 5-year survival rate was estimated 71% in patients with vitreoretinal lymphoma in our observation. Significantly longer 5-year overall survival (P˂0.01) was observed in patients with vitreoretinal lymphoma compared with patients with primary CNS lymphoma without vitreoretinal involvement. Progression-free survival was almost equal in both groups of patients with primary vitreoretinal lymphoma and primary CNS lymphoma (P=0.363). The relapse of lymphoma was frequent (50%–60%) with the median time to first relapse of 31 months. Combined treatment (local and systemic) in patients without CNS involvement significantly prolonged progression-free survival in our study (P˂0.05). Conclusion: Combined treatment of primary vitreoretinal lymphoma significantly delays the relapse of lymphoma compared with local therapy alone. Intraocular involvement brings significant positive prognostic value when overall survival is compared.